Attachment style and father-child brain-to-brain synchrony : a hyperscanning study - Siti Syazana Abdul Halim (Nanyang Technological University, 2020)
Adult attachment style indicates the perception an adult has towards their interpersonal relationships. Present literature often highlights mother-child attachment theories, though fathers play a vital role in a child’s life as well. We believe that father’s attachment style will influence father-child brain-to-brain synchrony. This study utilized the Attachment Style Questionnaire (ASQ) to measure father’s inclination towards social relations with others, with five subscales underpinning the overarching categories of secure and insecure attachment styles. 29 father-child dyads were recruited in our tandem hyperscanning study, in which they were required to watch three 1-min video clips from the movies ‘Brave’, ‘Peppa Pig’ and ‘The Incredibles’ together. Functional near-infrared spectroscopy (fNIRS) was used as a tool to measure brain activity, focusing on the prefrontal cortex (PFC) regions. We then employed the Dynamic Time Warping (DTW) algorithm to observe the level of similarity between two temporal sequences and measure father-child brain-to-brain synchrony, allowing us to infer whether there was a synchronous psychophysiological pattern within a father-child dyad. Results indicate an interesting outlook on the association between father’s attachment style and brain synchrony. We found a significant association between father’s preoccupation with relationships and brain synchrony in the right lateral PFC region of Brodmann Area 46 (BA46). This finding proposes that the more preoccupied fathers are with relationships, the more they are able to offer support to their child in developing self-regulatory strategies. We hope to offer a deeper insight on the connection between a father and child, therefore invigorating research on father-child attachment.